THE INFLUENCE OF WORK CONFLICT, PERSONAL VALUES TOWARD INTENTION TO WORK: MODERATED BY SOCIOEMOTIONAL WEALTH - Setiowati, Maria Henny; Tambunan, Damelina Basauli (Review of Management and Entrepreneurship, 2023)
The background of this study is that many family businesses have difficulty surviving from generation to generation due to the difficult decisions taken to maintain business continuity which failed in the succession process. Therefore, the aim of this research is to test the influence of work conflicts, personal values toward intention to work in family business moderated by socioemotional wealth. The sample used totaled 40 samples which choose by using purposive sampling method with some criteria. Data analyzed by using partial least square (PLS) and the results of this study conclude that work conflict in family business (X1) has a significant but negative effect to intention to work in family business (Y); personal values (X2) has a positive and significant effect to intention to work in family business (Y); and socio-emotional wealth (M) affects and strengthening the relationship between X1 and X2 toward Y